Determinants of financial performance of banks in Central and Eastern Europe - Antoun, Roger; Coskun, Ali; Georgevski, Bojan (Business and economic horizons, 2018)
The aim of this study is to investigate the bank-specific, industry-specific, and macroeconomic determinants of the financial performance of banks in Central and Eastern European Countries. For this purpose, first we determined the factors affecting performance, based on findings in the literature. We constructed a financial performance index (FPI) based on CAMEL ratios and then ran the computed index on the aforementioned determinants. In the analysis, we used unbalanced panel data covering the period 2009–2014, which were collected from from the Bankscope database, World Development Indicators, and the Financial Structure and Development Dataset. We conducted an empirical analysis using fixed-effect panel regression. Our results suggest that the asset quality and earnings of banks are negatively affected by size, and positively affected by business mix and inflation. Capital adequacy and liquidity were found to be negatively affected by size and positively affected by bank concentration and economic growth.